Circulating TNFSF14 (Tumor Necrosis Factor Superfamily 14) Predicts Clinical Outcome in Patients With Stable Coronary Artery Disease. Issue 6 (June 2019) - Hsu, Chien-Yi; Tseng, Wei-Kung; Wu, Yen-Wen; Lin, Tsung-Hsien; Yeh, Hung-I.; Chang, Kuan-Cheng; Wang, Ji-Hung; Chou, Ruey-Hsing; Huang, Chun-Yao; Huang, Po-Hsun; Leu, Hsin-Bang; Yin, Wei-Hsian; et al.
Abstract : Objective—: Basic research indicates that TNFSF14 (tumor necrosis factor superfamily 14) may be involved in the pathogenesis of atherosclerosis. Given the requirements of new biomarkers for risk classification in coronary artery disease (CAD), we conducted a longitudinal analysis to investigate if TNFSF14 levels are associated with the risk of cardiovascular events among patients with stable CAD. Approach and Results—: In total, 894 patients with CAD were enrolled in a multicenter prospective study. The primary outcome was the occurrence of cardiovascular death, nonfatal myocardial infarction, and stroke. The secondary outcome was the occurrence of all-cause death, nonfatal myocardial infarction, stroke, revascularization, and hospitalization because of angina or heart failure. During the mean follow-up period of 22±9 months, 32 patients reached the primary outcome and 166 patients reached the secondary outcome. Kaplan-Meier analysis showed that the event-free survival was significantly different in the first and fourth quartile groups in subjects categorized by TNFSF14 levels. In multivariate Cox proportional hazard regression analysis, TNFSF14 was independently associated with the risk of cardiovascular events after adjustment for various relevant factors (adjusted hazard ratio, 1.14; 95% CI, 1.04–1.25). In the validation cohort of 126 multivessel patients with CAD, TNFSF14 was confirmed to provide good prognostic predictive value for composite cardiovascular events (adjusted hazard ratio, 1.11; 95% CI, 1.04–1.19). Conclusions—: This is the first study to demonstrate that increased TNFSF14 levels were independently associated with the occurrence of cardiovascular events in patients with stable CAD. Future studies are worthy to validate if TNFSF14 could be a novel prognostic biomarker for CAD outcomes over different populations. Abstract : Supplemental Digital Content is available in the text.